Subclinical Burden of Coronary Artery Calcium in Patients With Coarctation of the Aorta - Krishnamurthy, Yamini; Schmidt, Ada C. Stefanescu; Bittner, Daniel O.; Scholtz, Jan-Erik; Bui, Amy; Reddy, Rajesh; Youniss, Mohamed A.; Donohoe, Kendall; Flannery, Laura D.; Fahed, Akl C.; Ghoshhajra, Brian B.; Yeh, Doreen Defaria; et al. (American Journal of Cardiology, 2019)
Coronary computed tomography (CT) angiography is often performed in adults with coarctation of the aorta (CoA) for anatomic assessment. As this population ages, assessment of atherosclerotic cardiovascular disease burden is important. Thus, quantitative and qualitative coronary artery calcium (CAC) scores were assessed for patients with CoA >= 16 years of age, who were seen at a referral center. CoA patients had either coronary CT angiography or chest CT with interpretable coronary information performed for clinical indications (follow-up, preoperative, or for symptoms) from 2004 to 2017. Qualitative CAC was determined based on low-dose CT and lung cancer screening protocols. Quantitative CAC scores were compared with an age- and gender-matched control cohort of patients chosen from an emergency department database of patients who received coronary CT angiography for chest pain evaluation. Atherosclerotic cardiovascular disease 10-year predicted risk scores were calculated for both cohorts. Out of 131 patients with CoA (mean age 46.1 +/- 15.3 years), 22 patients (17%) had multivessel atherosclerotic disease on qualitative assessment. In the subgroup of patients >= 40 years, those with CoA were more likely to have a quantitative CAC score >= 400 compared with those without CoA (14% vs 4%, p = 0.02). Median atherosclerotic cardiovascular disease risk score was 8% (interquartile range 2% to 12%) for CoA patients >= 40 years, and 5% (interquartile range 2% to 9%) for patient without CoA >= 40 years. In conclusion, we determined that CoA patients have subclinical atherosclerosis identifiable on CT in high rates when compared with patients without CoA. Atherosclerotic cardiovascular disease should be assessed in these patients for prevention and treatment. (C) 2018 Published by Elsevier Inc.
CRIS-Team WoS Importer:2019-05-21